Sistema Integrado de Gestão: uma proposta de modernização no processo de aquisição e controle de bens móveis do Colégio Técnico Industrial de Santa Maria - Bathaglini, Maikel Guerra (2023)
This research discusses a model of Integrated Management System, which seeks to modernize the process of acquisition and control of movable assets of technical college Industrial of Santa Maria (CTISM). The research theme focuses on proposing the development of an Integrated Management System, which will be applied in CTISM. The interest was in diagnosing the asset management situation in the unit, identifying its limitations and, based on this, proposing the development of an Integrated Management System using information technology resources, which covered all phases of the process, from the request for opening a bidding process, going through the acquisition phase, until the final destination of the asset in the teaching unit (patrimonial control). The proposed system seeks to facilitate access to information, be dynamic, efficient, effective and able to integrate the internal agents involved in its planning, helping in decision-making. As a methodology, the research is descriptive, of a qualitative nature, of the case study type, and was developed in three main stages: mapping of the Bidding Request, Purchase Request and Asset Control processes in execution at the unit, the second stage sought to map the processes already with the incorporation of the Integrated Management System in these flows, and finally, the third stage consisted of identifying what would be its functionalities and what benefits the system would bring to the users of the system. As a result, the research obtained an Integrated Management System model that seeks to better satisfy the needs of users, improve asset management, integrate information and facilitate access to them, optimize work routines, provide greater transparency to processes, in addition to be a decision support tool. The model can be shared with the other teaching units of the Federal University of Santa Maria (UFSM).